Safety and outcomes of endoscopic ultrasound-guided drainage for malignant biliary obstruction using cautery-enabled lumen-apposing metal stent - Chin, Jerry Yung-Lun; Seleq, Samir; Weilert, Frank (Endoscopy International Open, 2020)
Background and study aims There is increasing evidence to suggest that EUS-guided biliary drainage (EUS-BD) is a safe and effective treatment alternative for patients with malignant biliary obstructions (MBOs) after failed endoscopic retrograde cholangiopancreatography. Patients and methods We performed a retrospective analysis of data prospectively collected from patients with MBO who underwent choledochoduodenostomy (CDS) or gallbladder drainage (GBD) between August 2016 and June 2020 using the electrocautery-enabled lumen-apposing metal stents (ECE-LAMS). The primary endpoint was technical and clinical success. Secondary endpoints were adverse events (AEs) and reinterventions. Results A total of 60 patients were included in the study, with 56 CDS and 4 GBD. Median age was 76 years with 57 % male (34/60). The most common indication for EUS-BD was pancreatic cancer (78 %). Technical success was achieved in 100 % of cases, with a clinical success rate of 91.7 %. Mean total bilirubin pre-procedure was 202 umol/L (normal < 20 umol/L) and 63.8 umol/L post procedure (P < .001). Twenty-one patients had bilirubin recorded at 2 weeks post EUS-BD with 20 of 21 patients demonstrating > 50 % reduction in bilirubin (mean bilirubin reduction 75 %). AEs occurred in 12 of 60 patients (20 %), all of which were mild. The reintervention rate was 11.7 % (7/60). Stent occlusion occurred in 10 of 60 patients (16.7 %) with a mean time to stent occlusion of 46.2 days (3–133). Stent patency of 83.3 % was observed with a mean follow up of 7.9 months. Conclusion EUS-CDS and GBD using ECE-LAMS are effective EUS-based techniques for managing patients with MBO. AEs are usually mild and resolved by reintervention.